PENCITRAAN STRUKTUR LAPISAN BAWAH TANAH DAN DETEKSI LAPISAN TERSEMBUNYI DI SITUS PEMBANGUNAN KILANG MINYAK TUBAN DENGAN MENGGUNAKAN TOMOGRAFI SEISMIK REFRAKSIP - Julfianto, Genadi
In Civil Engineering, geophysics is often used to learn the conditions of ground, bedrocks, or even the ground water on the construction sites, aside from that, geophysics is also used to determine the feasibility of the construction sites and to set the construction’s most effective design. In this research, an underground model will be made for the Tuban oil rig’s construction, and a detection of hidden layer, a thin layer which is not typically read by the seismograph, hence creating an error in interpretation, will also be conducted. In acquiring the data, the seismic refraction method, a method which uses the calculation of travel time of the refracted waves and waves propagating through the subsurface layers, will be done. The data acquisition was done on the Tuban district, the province of East Java from the 11th of October 2020 to the 23rd of October 2020. There were eight tracks to be measured, with varying lengths, on this research, a track lengthening up to approximately 2.1 kilometers will be used as the subject of the research, therefore a configuration of nineteen cable spreads will be used. The data acquisition was done by using two types of shot configurations, which are the end-off shot and the middle shot. The acquired data will then be processed by using the SeisImager 2D software. The method involved will be the seismic tomography method, which consists of inversion and the forward modelling. The final model will be a velocity model which will then be compared to Tuban’s geological map. According to the constructed velocity model, the research area had a few underground layers with differing velocities.